Penerapan Model Pembelajaran Problem Based Learning untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran IPA Kelas V SDK Saenama Kabupaten Malaka - Anastasia Seuk; Yohana Febriana Tabun; Damian Puling (Jurnal Cakrawala Pendidikan dan Biologi, 2024)
Application of the Problem Based Learning Model to Improve Student Learning Outcomes in Science Subjects in the Saenama VSDK Class for the 2023/2024 Academic Year. This researcher aims to improve student learning outcomes in science learning on Temperature and Heat material for class V SDK Saenama for the 2023/2024 Academic Year through the Problem Based Learning Model to Improve Student Learning Outcomes. This research is classroom action research. Which was carried out at SDK Saenama from 13 to 18 November 2023 with the research subjects being students in class V of SDK Saenama for the 2023/2024 academic year, consisting of 20 students. Data collection techniques were carried out using learning results and student observation sheets using the Problem Based Learning learning model as well as learning tools in the form of syllabi, lesson plans and worksheets. The research results show an increase in student learning outcomes. Student learning outcomes can improve from average. The results of the research carried out show an increase in each aspect that has been determined. In the first cycle the percentage of completeness was 25% in the not yet category and in the second cycle it increased to 95% in the very good category. From these results it can be concluded that the application of the Problem Based Learning model to improve student learning outcomes in science subjects in the VSDK Saenama class for the 2023/2024 academic year has increased.